Development of Video-Based Learning Media on SLETV Material to Improve Mathematics Learning Outcomes - Kusumah, Siska Widia (Contemporary Education and Community Engagement (CECE), 2024)
This study aims to determine the impact of using video learning media on improving the learning outcomes of eighth-grade students. Employing a Research and Development (R&D) approach, the study utilizes the ARCS research model, which encompasses student attention to the product (attention), assessment of product relevance (relevance), student confidence in using the product (confidence), and student satisfaction with the product (satisfaction). Data collection techniques include observations and structured questionnaires. The sample consists of eighth-grade students selected through purposive sampling. The research procedure involves needs analysis, design, and development of the video learning media using the Renderforest application, implementation in classroom settings, and evaluation through collected data. Descriptive statistics summarize students' responses, while paired sample t-tests compare pretest and posttest scores to assess learning improvements. The study reveals that video learning media significantly enhances student engagement, comprehension of SLETV material, and overall satisfaction with learning. The findings underscore the importance of integrating motivational elements into educational media to foster better academic outcomes. This research contributes to understanding digital learning tools in education, offering practical insights for educators to enhance student learning experiences through innovative media.